1999
DOI: 10.3354/ame019307
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylsulfide (DMS) production by size-fractionated particles in the Labrador Sea

Abstract: We measured the production of dimethylsulfide (DMS) by size-fractionated particles during a cruise in the Labrador Sea in May-June 1997. The experiments were conducted at 2 stations characterised by low levels of nitrate and high levels of phytoplankton biomass and particulate dirnethylsulfo~~~opropionate (DMSP,). Samples were size fractionated to assess the size distribution of DMSPp and the potential DMS production associated with the different size fractions. The potential for DMS production was estimated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Ledyard & Dacey (1994) speculated that this might indicate that bacteria are adapted to high DMSP d concentrations such as might be found in close association with cells and particles. This is supported by the observation by Cantin et al (1999) that high potential rates of DMS production are associated with the particulate fraction in natural seawater samples. Microenvironments of high dissolved organic carbon concentration are postulated to exist around phytoplankton cells and in aggregates of marine snow (Azam & Ammerman 1984, Mitchell et al 1985, Bowen et al 1993, Blackburn et al 1998.…”
Section: Short-term Kinetics Of Dms Productionsupporting
confidence: 69%
“…Ledyard & Dacey (1994) speculated that this might indicate that bacteria are adapted to high DMSP d concentrations such as might be found in close association with cells and particles. This is supported by the observation by Cantin et al (1999) that high potential rates of DMS production are associated with the particulate fraction in natural seawater samples. Microenvironments of high dissolved organic carbon concentration are postulated to exist around phytoplankton cells and in aggregates of marine snow (Azam & Ammerman 1984, Mitchell et al 1985, Bowen et al 1993, Blackburn et al 1998.…”
Section: Short-term Kinetics Of Dms Productionsupporting
confidence: 69%
“…The latter was taken to suggest that algal DMSP lyase "may contribute significantly to DMS production from DMSPp during bloom situations in the field." This and other studies (19) indicate that bacteria accompanying phytoplankton blooms, such as these high DMSPp-containing colonial forms, are not responsible for all the DMS produced during senescence. Finally, evidence indicates that phytoplankton senescence and the concomitant DMS production are linked to nutrient deficiency (97), which is believed to be responsible for the "crash" of most blooms.…”
Section: Linking Phytoplankton Dmsp To the Microbial Food Webmentioning
confidence: 83%
“…The number of these epiphytes that were DMSP utilizers is unknown. In another study, phytoplankton particles Ͼ20 m in size had high rates of DMS production (from added DMSP) compared to 0.7-to 2-m-sized particles (free-living bacteria), which were negligible (19). The higher rates of DMS production by the larger particles were due either to attached bacteria or to the size of the phytoplankton cells; the researchers speculated that it might be due to attached bacteria.…”
Section: Bacterial Degradation Of Dmspmentioning
confidence: 97%
See 1 more Smart Citation
“…Niki et al (2000) calculated that the algal lyase pathway is as important as the bacterial lyase pathway, in samples from Tokyo Bay. Also other size fractionation experiments have shown that lyase activity is often associated with the large size fractions (Cantin et al 1999;Scarratt et al 2000), although it cannot be excluded that attached bacteria are partly responsible for this activity. In a modelling study of the seasonal evolution of DMS in the Southern Bight of the North Sea, van den Berg et al (1996) showed that the presence of an algal DMSP-lyase associated with the occurrence of Phaeocystis was essential to properly describe the DMS spring peak.…”
Section: Maintenance Of Intracellular Dmsp Concentration: Algal Dmsp-mentioning
confidence: 99%